Characterization of persistent materials of deposited PM2.5 in the human lung. (August 2022) - Shamsollahi, Hamid Reza; Yunesian, Masud; Kharrazi, Sharmin; Jahanbin, Behnaz; Nazmara, Shahrokh; Rafieian, Shahab; Dehghani, Mohammad Hadi
Abstract: Clearance of deposited urban air particulates (PMs) from the lung is vital for the protection of the lung tissue. Several studies have investigated the behavior of immune cells against these particulates in vitro and in vivo . However, the fate of particulates in the lung is yet unclear. Here, we report the results of our investigations on the clearance of particulates from the lung. Twelve normal lung tissue samples were taken from nonsmoking and non-occupationally exposed patients who needed lung lobectomy or segmentectomy. The remaining particulates were isolated from the alveolar area and extracellular matrix (ECM), separately, and their chemical composition was determined using the FE-SEM EDAX and GC-MS. Moreover, urban air PM2.5 was collected in two forms dry and washed. These were characterized too. Our results showed that none of the metals in the deposited particulates structure is fully water-soluble. After contact with mucosal liquid, the alveolar particulates included Fe, Al, Si, Ti, and Ni. These elements were absent in the PMs isolated from ECM. The organics of alveolar and ECM particulates were the same and included tetra-decane, hexadecane, and octa-decane. None of the organics present in the urban air PM2.5, such as PAHs, were available in isolated particulates from the lung tissue. This study shows that the full clearance of inhaled particulates does not happen in the lung. The immune system's primary function is detoxification by removing all components identifiable by immune cells. After that, the remained PMs will be relocated and deposited into the ECM. Graphical abstract: Image 1 Highlights: The first human evidence about fate of urban air PMs in the human lung. New evidences about changes in PMs' components in the human lung. Confirmation of incomplete clearance of deposited PMs from the human lung.